Macrophage Polarization and the Regulation of Bone Immunity in Bone Homeostasis - Hu K; Shang Z; Yang X; Zhang Y; Cao L (Dove Medical Press, 2023)
Kangyi Hu, Zhengya Shang, Xiaorui Yang, Yongjie Zhang, Linzhong Cao Clinical College of Traditional Chinese Medicine, Gansu University of Chinese Medicine, Lanzhou, People's Republic of ChinaCorrespondence: Linzhong Cao, Clinical College of Traditional Chinese Medicine, Gansu University of Chinese Medicine, Lanzhou, 73000, People's Republic of China, Email 258773304@qq.comAbstract: Bone homeostasis is a dynamic equilibrium state of bone formation and absorption, ensuring skeletal development and repair. Bone immunity encompasses all aspects of the intersection between the skeletal and immune systems, including various signaling pathways, cytokines, and the crosstalk between immune cells and bone cells under both homeostatic and pathological conditions. Therefore, as key cell types in bone immunity, macrophages can polarize into classical pro-inflammatory M1 macrophages and alternative anti-inflammatory M2 macrophages under the influence of the body environment, participating in the regulation of bone metabolism and playing various roles in bone homeostasis. M1 macrophages can not only act as precursors of osteoclasts (OCs), differentiate into mature OCs, but also secrete pro-inflammatory cytokines to promote bone resorption; while M2 macrophages secrete osteogenic factors, stimulating the differentiation and mineralization of osteoblast precursors and mesenchymal stem cells (MSCs), and subsequently increase bone formation. Once the polarization of macrophages is imbalanced, the resulting immune dysregulation will cause inflammatory stimulation, and release a large amount of inflammatory factors affecting bone metabolism, leading to pathological conditions such as osteoporosis (OP), rheumatoid arthritis (RA), and steroid-induced femoral head necrosis (SANFH). In this review, we introduce the signaling pathways and related factors of macrophage polarization, as well as their relationships with immune factors, OB, OC, and MSC. We also discuss the roles of macrophage polarization and bone immunity in various diseases of bone homeostasis imbalance, as well as the factors regulating them, which may help to develop new methods for treating bone metabolic disorders.Keywords: M1 macrophage, M2 macrophage, bone immunity, bone homeostasis